2022
DOI: 10.1088/2399-6528/ac5f5f
|View full text |Cite
|
Sign up to set email alerts
|

Low collision energy mutual neutralization reaction of He+ and H

Abstract: A Semi-classical Landau-Zener model is employed to theoretically study mutual neutralization in the collisions of $\mathrm{^4He^+}$ and $\mathrm{H^-}$/$\mathrm{D^-}$. The model includes ten covalent states and an ion-pair state of $\mathrm{^2\Sigma^+}$ symmetry for the $\mathrm{HeH}$ molecular system. Here the assumption is that only two states are interacting at a given internuclear position. In the diabatic representation, the nuclear dynamics relevant for mutual neutralization is modelled for collision ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The neglected rotational and translational factors could also be contributing to the discrepancy. A discrepancy between the fully quantum study and the semi-classical model has recently been observed for the mutual neutralization of process [21] . The treatment of the radial velocity, , at the curve crossing classically leads to a wrong asymptotic dependence of the reaction cross section on , rather than [7] .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The neglected rotational and translational factors could also be contributing to the discrepancy. A discrepancy between the fully quantum study and the semi-classical model has recently been observed for the mutual neutralization of process [21] . The treatment of the radial velocity, , at the curve crossing classically leads to a wrong asymptotic dependence of the reaction cross section on , rather than [7] .…”
Section: Discussionmentioning
confidence: 95%
“…This is proving a challenge to adequately undertake, in particular for systems with many electrons. On the other hand, the Landau-Zener model [17] , [18] , can provide mutual neutralization reaction cross sections that are comparable with the fully quantum studies [16] , [19] , [20] , [21] . The Landau-Zener model is only dependent upon parameters like the asymptotic energies for the states involved, electronic couplings and the crossing distance.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation